Higher education supply, neighbourhood effects and economic welfare - Elena Cottini; Paolo Ghinetti; Simone Moriconi (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2019)
This paper uses an own built dataset on the history of universities in Italy during 1861-2010 to estimate neighbourhood effects in the local supply of higher education, and incorporate them in a welfare analysis. We implement an instrumental variables approach that exploits initial conditions in the pre-unitarian Italian states, interacted with post-unification university reforms. We provide robust evidence of local displacement between higher education supply in neighbouring provinces. These effects are mostly concentrated within the same field of study, the same region, and a spatial reach of 90 Km. We show that accounting for these displacement forces is important to evaluate the local economic returns related to higher education supply. On average, these explain more than 4% of local value added per capita. Economic returns are very localised, and larger in provinces that host university hubs.
Keywords: I23; I28; N00; R1; 330; neighbourhood effects; higher education supply; historical data; initial conditions; economic welfare